Weed-ing the Roots: Constructing Immigrant Identity in A.M. Bakalar’s Madame Mephisto (2012) - Bryla, Martyna Marika (My University, 2014)
Poles are one of the three largest non-UK born ethnic groups in all countries and most regions of the United Kingdom. Since Poland’s accession to the European Union in May 2004, thousands of Poles have come to the UK in search of better job prospects and higher standards of living. For many of them London has been the ultimate destination, promising not only a booming job market but also embodying “a modern, transcultural metropolis” (Plesske and Rostek 1). Therefore, it comes as no surprise that Polish migrant experience in the UK and London in particular has found its way into fiction. One example is A.M. Bakalar’s debut novel Madame Mephisto (2012), advertised as the voice of the new wave of Polish immigration and the first novel to be written in English by a Polish female author since Poland joined the EU in 2004. This paper focuses on the novel’s protagonist, a thirty-year-old Pole named Magda, and the way she constructs her immigrant identity through defying her Polishness and taking the opportunities London offers to an extreme degree. By becoming a ruthless cannabis dealer, Magda asserts her independence and challenges the stereotype of a docile Polish female for whom the family and religion are of utmost importance. At the same time, she perpetuates other stereotypes related to gender, ethnicity and, in a broader perspective, the conceptual categories of East and West. In contrast to more traditional migrant fiction, it is the protagonist’s homeland rather than the British “other” that seems to be the source of Magda’s emotional malaise. By analyzing the novel as well as several interviews with the author and the book’s reception both in Poland and in the UK, this paper inquiries into the nature of contemporary migrant experience as negotiated through fiction. It also poses questions about what it means to integrate and whether severing ties with one’s native culture is necessary to achieve it.
Keywords: Novela inglesa; Identidad étnica